Analysis Quality Value of Rice Agro-Industry in Agam District - Nofalia, Wira; Santosa; Yulianto, Kiki (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The rice agro-industry is a business that carries out post-harvest handling activities in the form of drying processes, processing grain into rice, and marketing rice. In the grain drying process, it is necessary to pay attention to the moisture content so that the rice produced is of high quality. The grain moisture content that must be achieved for grain storage and milling is 14%. This study aims to analyze the quality characteristics of rice in Agam Regency. This research used a purposive sampling method. The results showed that the water content of rice in Agam Regency ranged from 12.05- 13.41% and the quality of rice in Agam Regency was classified as medium rice with a head grain range of 76-82%, while the SNI 6128 2020 standard for premium rice on the head grain was at least 85%. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 17: Partnerships for the Goals